2000
DOI: 10.1088/0967-3334/21/3/301
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory monitoring using an air-mattress system

Abstract: This paper describes a non-invasive respiratory monitoring system using an air mattress. The air-mattress system features multiple air compartments to monitor movements of the thorax and the abdomen separately. To evaluate the performance of the air-mattress system, four subjects were selected for the study and their separate ribcage and abdominal movements were monitored simultaneously by respiratory inductive phlethysmography belts and the air-mattress system. The sensitivity and accuracy indices of the air-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…Respiratory rate is out of step with the other vital signs, which are measured electronically. There is a long list of proposed alternatives: capnography by mask, nasal prongs, or mouthpiece [30][31][32] ; pneumotachography (direct flow measurement) by mask or mouthpiece 33,34 ; acoustic monitoring by nasal microphones 30,35 ; nasal thermistors (temperature) 18,34,36 ; fiberoptic nasal sensors that gauge condensation during exhalation 30,37,38 ; inductive plethysmography, which measures chest wall and abdominal movement by bands encircling the trunk (extensometry) 26,33 ; single-compartment and multicompartment air mattresses that measure and compare chest and abdominal volumes [39][40][41] ; mask-mounted pyroelectric polymer strips, which detect temperature variations 32,42 ; transdermal fiberoptic photoplethysmography 30,43,44 ; and transthoracic impedance plethysmography. 13,18,26,30,32,37,[45][46][47] All of the above-mentioned modalities have been reported to correlate well with ''criterion standard'' clinical measurement of respiratory rate.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rate is out of step with the other vital signs, which are measured electronically. There is a long list of proposed alternatives: capnography by mask, nasal prongs, or mouthpiece [30][31][32] ; pneumotachography (direct flow measurement) by mask or mouthpiece 33,34 ; acoustic monitoring by nasal microphones 30,35 ; nasal thermistors (temperature) 18,34,36 ; fiberoptic nasal sensors that gauge condensation during exhalation 30,37,38 ; inductive plethysmography, which measures chest wall and abdominal movement by bands encircling the trunk (extensometry) 26,33 ; single-compartment and multicompartment air mattresses that measure and compare chest and abdominal volumes [39][40][41] ; mask-mounted pyroelectric polymer strips, which detect temperature variations 32,42 ; transdermal fiberoptic photoplethysmography 30,43,44 ; and transthoracic impedance plethysmography. 13,18,26,30,32,37,[45][46][47] All of the above-mentioned modalities have been reported to correlate well with ''criterion standard'' clinical measurement of respiratory rate.…”
Section: Discussionmentioning
confidence: 99%
“…Piezoelectric sensor-based BCG monitoring systems were used for the unconstrained acquisition of N-N intervals. With a growing need for long-term monitoring techniques in sleep studies, ballistocardiography has been suggested as a measure for providing information on cardiac activity without disturbing sleep in an out-of-sleep laboratory environment [13,14,17,18,19,20,21,22,23,24]. Many previous studies validated the usefulness of ballistocardiography for overnight heartbeat monitoring [14,17,18,19,20,22,23]; however, no study has attempted to use ballistocardiographic recording for the unconstrained estimation of the ODI.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other semiquantitative methods are used, although less frequently, to detect respiratory movements during sleep, as follows: thoracic impedance, electromyography of the respiratory muscles or the air-mattress system [29][30][31][32][33].…”
Section: Thoraco-abdominal Bandsmentioning
confidence: 99%